Association of coronary high-intensity plaque on T1-weighted magnetic resonance imaging and circulating malondialdehyde-modified low-density lipoprotein levels with cardiac events. (25th November 2020) - Hiraya, D; Sato, A; Hoshi, T; Watabe, H; Ieda, M
Abstract: Background: Although elevated oxidized low-density lipoprotein could play critical roles in vulnerable plaque, there are no studies that compared coronary high-intensity plaque (HIP) on non-contrast T1-weighted magnetic resonance imaging (T1WI_MRI) and circulating malondialdehyde-modified low-density lipoprotein (MDA-LDL) levels for the prediction of cardiac events. Methods and results: A total of 139 patients with coronary artery stenosis (>70%) were examined with non-contrast T1WI using a 1.5-T MRI (HIP: n=63, non-HIP: n=76). Scheduled percutaneous coronary intervention (PCI) for culprit lesions was performed within 48 h after MRI. HIP was defined as a signal intensity of coronary plaque to cardiac muscle ratio (PMR) of ≥1.4. At admission, circulating levels of MDA-LDL and other lipid-related markers were measured. We evaluated the subsequent cardiac events, which were defined as major adverse cardiac events (MACE; cardiac death, myocardial infarction, and/or ischemia-driven PCI) during follow-up periods (5.6±1.3 years). Circulating MDA-LDL levels were significantly higher in patients with HIP than in those without HIP (p<0.0001). MDA-LDL levels were significantly correlated with PMR (r=0.490, p<0.0001). In multivariable logistic regression analysis, MDA-LDL levels were independently associated with the presence of HIP (OR 1.05; 95% CI, 1.02–1.08, p<0.0001). The incidence of MACE was significantly higher in patients with HIP (27%) than in those without HIP (5%; p=0.011 by the log-rank test). In the multivariable Cox proportional hazard analysis, the MDA-LDL levels (HR 1.03; 95% CI:1.01–1.05, p=0.007) and PMR (HR 2.39; 95% CI:1.19–4.65, p=0.016) were significantly associated with MACE. For MACE prediction, the C-statistic values for MDA-LDL, PMR, and PMR+MDA-LDL were 0.724, 0.791, and 0.800, respectively. Compared with MDA-LDL alone, the addition of PMR to MDA-LDL increased the net reclassification improvement by 0.78 (p=0.012). Conclusions: MDA-LDL levels might be associated with the presence of HIP in patients with coronary artery disease. Furthermore, adding PMR to MDA-LDL levels markedly improved MACE prediction. Funding Acknowledgement: Type of funding source: None